Effectiveness of a Model of Care for Diabetis Mellitus Patient Who Could not Control Blood Sugar - Theeraakarawipas, Narapong (Journal of Health Science of Thailand, 2019)
The objectives of this research were to study effectiveness of a care model for diabetic patients who could not control blood sugar and to assess their satisfaction with the model. The samples were 80 uncontrolled diabetic patients. They were divided into 2 groups: the study group and the control; each group consisted of 40 people. The care model was applied for the study group where as the routine care services were provided to the control group. The study tools were questionnaire, diabetic care model, pre- and post-test to assess the outcomes with regard to clinical data and the satisfaction of the patients. The data were analyzed by descriptive statistic, Chi-square test, independent and paired sample t-tests. It was found that after the model implemtation, the study group had higher average diabetes mellitus knowledge score and desirable self-care behavior than those before using the model; and significant decline of blood sugar level was observed (p<0.05). Similar findings were also identified when compare the study group with the control. Moreover, 87.5 percent of users had satisfaction regarding to diabetic caring model at high level and 12.5 percent satisfied at moderate level to the use of self-care model. In addition, the patients in the study group had express their satisfaction on the model, 87.5% at high level and 12.5% at moderate level. Thus, the diabetis mellitus care model which had been developed had good effectiveness and high patient satisfaction. Furthermore, it was feasible to implement in a hospital setting. Therefore, the model should be widely applied in order to improve effectiveness of care for patients with diabetes mellitus.